GEOGRAPHICAL ANALYSIS OF TEMAJUK TOURIST VILLAGE DESTINATIONS - Sobirin, Sobirin; Buwono, Sri; Anasi, Putri Tipa (GEOREFERENCE, 2024)
This research is entitled Geographical Analysis of Temajuk Tourism Village Destinations. Temajuk Village is one of the villages in Sambas Regency with enormous potential in the tourism sector, so  Temajuk Village was developed into a tourist village. Temajuk is set to become a tourist village on August 9, 2021, regulated in Keputusan Bupati Sambas Number 443/DISPARPORA/2021. Apart from the potential, the development of the Temajuk Tourism Village is also seen from the geographical factors that influence it. This study uses qualitative methods with descriptive analysis. The data sources for this research are research objects in the Temajuk Tourism Village and the data are the results of field observations and the results of interviews with village heads, managers, and visitors. The results of this study indicate that geographical factors play a significant role in the development of Temajuk Village to become a tourism village. These factors include location, distance, affordability, agglomeration, pattern, morphology, usability value, interaction, area differentiation, and spatial linkages. Besides that, the condition of tourism objects in Temajuk Village is quite good and the facilities are also quite good, but there are still some that are inadequate.